Sapropterin Treatment Prevents Congenital Heart Defects Induced by Pregestational Diabetes Mellitus in Mice - Anish Engineer; Tana Saiyin; Xiangru Lu; Andrew S. Kucey; Brad L. Urquhart; Thomas A. Drysdale; Kambiz Norozi; Qingping Feng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Tetrahydrobiopterin is a cofactor of endothelial NO synthase (eNOS), which is critical to embryonic heart development. We aimed to study the effects of sapropterin (Kuvan), an orally active synthetic form of tetrahydrobiopterin on eNOS uncoupling and congenital heart defects (CHDs) induced by pregestational diabetes mellitus in mice. Methods and Results Adult female mice were induced to pregestational diabetes mellitus by streptozotocin and bred with normal male mice to produce offspring. Pregnant mice were treated with sapropterin or vehicle during gestation. CHDs were identified by histological analysis. Cell proliferation, eNOS dimerization, and reactive oxygen species production were assessed in the fetal heart. Pregestational diabetes mellitus results in a spectrum of CHDs in their offspring. Oral treatment with sapropterin in the diabetic dams significantly decreased the incidence of CHDs from 59% to 27%, and major abnormalities, such as atrioventricular septal defect and double‐outlet right ventricle, were absent in the sapropterin‐treated group. Lineage tracing reveals that pregestational diabetes mellitus results in decreased commitment of second heart field progenitors to the outflow tract, endocardial cushions, and ventricular myocardium of the fetal heart. Notably, decreased cell proliferation and cardiac transcription factor expression induced by maternal diabetes mellitus were normalized with sapropterin treatment. Furthermore, sapropterin administration in the diabetic dams increased eNOS dimerization and lowered reactive oxygen species levels in the fetal heart. Conclusions Sapropterin treatment in the diabetic mothers improves eNOS coupling, increases cell proliferation, and prevents the development of CHDs in the offspring. Thus, sapropterin may have therapeutic potential in preventing CHDs in pregestational diabetes mellitus.